Fatores associados ao sobrepeso e obesidade em uma comunidade quilombola no estado do Maranhão - FONTENELE, Dannylo Ferreira (2022)
Introduction: Obesity is already characterized as an epidemic and the concern of international health agencies with the problem is a frequent and growing agenda in the world health forums of the population. Excess body weight is one of the top five problems responsible for the overall burden of illness. This scenario has as its root cause the epidemiological and nutritional transition, with important impacts on the prevalence of diseases. Obesity is an important factor related to the group of chronic non-communicable diseases, which in turn are closely related to the social determinants of health. Social vulnerabilities tend to potentiate this scenario. The quilombola population as a group of important social vulnerability needs to beanalyzed as a target of this burden of illness. Objective: To analyze factors associated with weightand obesity in quilombolas in the State of Maranhão. Methodology: This is a retrospective, analytical and cross-sectional study with a quantitative approach. Secondary data were used. The classification variables were associated with the nonparametric chi-square test of independence. The numerical variables in relation to bmi classification were evaluated by the independent student t-test. The evaluation of the variables independent of sociodemographic conditions, life habits and health conditions in relation to the dependent variables BMI classification (normal and overweight/obese), classification of WC (normal and increased) and the classification of WHT (normal and increased) was made by multivariate logistic regression analysis. Results: The most frequent female population in the quilombola population analyzed, as well as the most prevalent age group between 30-39 years. In the family composition, the average number of children was 2.94. Regarding obesity-related risk factors by BMI classification, a significant effect of the individual's sex, consumption of salt, beans, vegetables and meat was found. The male individuals had a protective effect on obesity in relation to females. The use of more than one anthropometric indicator provided additional information to map the risk of chronic non- communicable diseases associated with overweight, WC and WHT. Conclusion: In this study it was possible to identify that the high prevalence reaches also vulnerable populations, such as quilombolas, presented high rates of overweight and obesity, more than 50% of the population investigated presented an increase in weight beyond the standard BMI. The nutritional risk associated with the presence of overweight and obesity becomes necessary to discuss, considering the current moment when food insecurity is currently growing in Brazil.